Key factors for advancing innovations to scale: Evidence from multiple country case studies of agricultural innovations - Kohl, Richard D. (Frontiers in Sustainable Food Systems, 2023)
Innovation pathways are composed of innovation, going to scale, and implementation at sustainable scale, where innovation is a new product, service or systems change not previously introduced in a specific context. They can take the form of new products or services, institutions, or systems change. Such pathways can play a lead role in transforming agri-food systems in low- and middle-income countries. Unfortunately, while there are many proposals in the published and grey literature for integrated, transformative approaches to innovation pathways, few have yet either gone to scale or been implemented sustainably at large scale. Here we assess whether there is evidence to support these proposals about how agricultural innovation pathways should be pursued. In this paper we identify from the literature and case studies ten potentially key factors for advancing scaling along the innovation pathway: participation, inclusion, leadership, iteration, adaptation, the specific attributes of innovation design, funding models, implementation models, systems change, and partnerships. We test these factors against a collection of innovation and scaling case studies from Bangladesh, Brazil, India, Kenya, Senegal, Uganda and Zambia. While the cases are somewhat limited in their reaching scale, the qualitative evidence presented in the cases confirms the general importance of these factors While this is not surprising , we also demonstrate their specific design and implementation (or absence), how each element contributes to success at large scale, and actionable examples to be applied in practice. The paper concludes that integrating these factors will require changes to traditional approaches to development, innovation and scaling in agri-food systems. Advancing along an innovation pathway to scale will require greater resources over longer time horizons. This implies focusing on fewer innovations at each phase and a greater appetite for risk and failure in individual cases, suggesting adoption of a portfolio rather than a project approach in evaluating success. This may lead to more unsuccessful individual efforts, but will be offset by a few transformative successes which will change the lives of hundreds of millions, if not billions.